T‐Wave Abnormality as Electrocardiographic Signature of Myocardial Edema in Non‐ST‐Elevation Acute Coronary Syndromes. Issue 3 (30th January 2018) - Cardona, Andrea; Zareba, Karolina M.; Nagaraja, Haikady N.; Schaal, Stephen F.; Simonetti, Orlando P.; Ambrosio, Giuseppe; Raman, Subha V.
Abstract : Background: T‐wave abnormalities are common during the acute phase of non‐ST‐segment elevation acute coronary syndromes, but mechanisms underlying their occurrence are unclear. We hypothesized that T‐wave abnormalities in the presentation of non‐ST‐segment elevation acute coronary syndromes correspond to the presence of myocardial edema. Methods and Results: Secondary analysis of a previously enrolled prospective cohort of patients presenting with non‐ST‐segment elevation acute coronary syndromes was conducted. Twelve‐lead electrocardiography (ECG) and cardiac magnetic resonance with T2‐weighted imaging were acquired before invasive coronary angiography. ECGs were classified dichotomously (ie, ischemic versus normal/nonischemic) and nominally according to patterns of presentation: no ST‐ or T‐wave abnormalities, isolated T‐wave abnormality, isolated ST depression, ST depression+T‐wave abnormality. Myocardial edema was determined by expert review of T2‐weighted images. Of 86 subjects (65% male, 59.4 years), 36 showed normal/nonischemic ECG, 25 isolated T‐wave abnormalities, 11 isolated ST depression, and 14 ST depression+T‐wave abnormality. Of 30 edema‐negative subjects, 24 (80%) had normal/nonischemic ECGs. Isolated T‐wave abnormality was significantly more prevalent in edema‐positive versus edema‐negative subjects (41.1% versus 6.7%, P =0.001). By multivariate analysis, an ischemic ECG showed a strong association with myocardial edema (odds ratio 12.23, 95% confidence interval 3.65‐40.94, P <0.0001). Among individual ECG profiles, isolated T‐wave abnormality was the single strongest predictor of myocardial edema (odds ratio 23.84, 95% confidence interval 4.30‐132, P <0.0001). Isolated T‐wave abnormality was highly specific (93%) but insensitive (43%) for detecting myocardial edema. Conclusions: T‐wave abnormalities in the setting of non‐ST‐segment elevation acute coronary syndromes are related to the presence of myocardial edema. High specificity of this ECG alteration identifies a change in ischemic myocardium associated with worse outcomes that is potentially reversible.